Nanotechnology : risk, ethics and law - Hunt, Geoffrey (Geoffrey Peter), 1947-; Mehta, Michael D., 1965- (Science in society series., 2006)
"Nanotechnology - technology at the molecular level - is held out by many as the Holy Grail for creating a trillion dollar economy and solving problems from curing cancer to reprocessing waste into products and building super fast computers. Yet, as with GMOs, many view nanotech as a high risk genie in a bottle that once uncorked has the potential to cause unpredictable, perhaps irreversible, environmental and public health disasters. With the race to bring products to market, there is pressing need to take stock of the situation and to have a full public debate about this new technological frontier. Including contributions by renowned figures such as Roland Clift, K. Eric Drexler and Arpad Pusztai, this is the first global overview of the state of nanotech and society in Europe, the USA, Japan and Canada, examining the ethics, the environmental and public health risks, and the governance and regulation of this most promising, and potentially most dangerous, of all technologies."--Book cover.